Factors on Fish Richness in Native Streams of Fogang Area, Qingyuan, Guangdong Province - Li, Shenglong (Transactions on Environment, Energy and Earth Sciences, 2024)
Rapid urbanization in the rural areas of Guangdong Province poses varying degrees of threat to the survival of native stream fishes. This study conducted over three years, utilized fishing nets, fish traps, angling techniques and lure-fishing methods to perform a quantitative assessment of stream fish species across 11 representative watersheds within Fogang County, Qingyuan City, Guangdong Province, along the upper reaches of the Pajiang River. In this study, a total of 4 orders, 4 suborders, 9 families, 4 subfamilies, 14 genera and 18 species of fish were collected. The identified species include Opsariichthys evolans, Opsariichthys bidens, Girella punctata, Acrossocheilus paradoxus, Pangasianodon hypophthalmus, Varicorhinus guangdongensis, Pseudogastromyzon fangi, Betta splendens, Micronemacheilus pulcher, Rhinogobius giurinus, Rhinogobius duospilus, Gambusia affinis, Pseudorasbora parva, Rhodeus ocellatus, Pseudorasbora pumila, Carassius auratus, Channa striata and Gobiocypris rarus. The dataset comprises 15 indigenous species and three non-indigenous species, namely the Girella punctata, Gambusia affinis and Channa striata. Based on comprehensive analysis of field surveys, fishing data and feeding data, it is evident that invasive alien species, environmental changes, water oxygen content and water quality exert significant influences on stream fish richness. Furthermore, variations in channel structure, river beds and coastal environments along the banks also contribute to alterations in species composition and diversity within aquatic ecosystems. Therefore, identifying factors that constrain the abundance of native stream fishes will help to protect the ecosystem as a whole, while restoring diversity and sustainability of the local aquatic communities and improving the living conditions and habitats of local population.